Bảo tồn tại chỗ di sản thiên nhiên và văn hóa khảo cổ hang động núi lửa ở Công viên địa chất toàn cầu Đắk Nông - La, Thế Phúc (Hà Nội, 2023)
Krong No volcanic cave system has been comprihensively studied all of three heritage values: geological heritage, biodiversity and cultural heritage since 2017 to present. On-site conservation of mentioned-above heritage values has been carried out in several of the caves of the studied area. In the frame of the TN17/T06 project, from the beginning, on-site conservation C6.1 volcanic cave was identified, towards geological-ecological-cultural tourism exploitation. To conservate archaeological cultural values, conservation of relics and artifacts in the excavation pits is paid special attention. This article introduces the initial successful results in researching and implementating on-site conservation of geological heritage values, biodiversity, and especially prehistoric archaeological heritage in volcanic cave of Vietnam. These results are lessons for the implementation of further cave conservation and serve as a basis for promoting natural and cultural heritages for sustainable tourism development in Dak Nong UNESCO Global Geopark.